Effect of vitamin D supplementation on metabolic syndrome and atherosclerosis biomarkers in epilepsy: a randomized controlled trial - Sri Handayani; Zen Hafy; Fitri Octaviana; Zulkhair Ali; Nita Parisa; Astri Budikayanti; Dessy Agustini; Radiyati Umi Partan (Medicinski glasnik, 2026)
Aim: To analyze the effect of vitamin D administration on serum 25(OH)D levels and biomarkers of metabolic syndrome and atherosclerosis (homeostatic model assessment of insulin resistance [HOMA-IR], adiponectin, homocysteine, and high sensitivity C-reactive protein [hs-CRP]) in epilepsy patients receiving enzymatic antiseizure medications (ASMs). Methods: This double-blind, randomized, placebo-controlled trial randomized 40 adult epilepsy patients treated with enzymatic ASMs to receive vitamin D3 (2,000 IU/day) or placebo for 12 weeks. The primary outcome was the change in serum 25-hydroxyvitamin D (25[OH]D) levels. Secondary outcomes included changes in HOMA-IR, adiponectin, homocysteine, and hs-CRP. Data were analyzed using a per-protocol approach. Results: Thirty-four patients completed the study. Vitamin D supplementation yielded a significantly greater increase in serum 25(OH)D (10.67 ± 8.16 vs. -1.29 ± 3.96 ng/mL; p < 0.001) and adiponectin (1.38 ± 3.05 vs. 0.34 ± 1.89 µg/mL; p = 0.045), as well as a significantly greater reduction in hs-CRP (-6.74 ± 14.65 vs. 1.81 ± 7.75 mg/L; p = 0.041) compared with placebo. Conversely, no significant differences were observed between groups regarding the changes in HOMA-IR (-0.24 ± 3.71 vs. -0.14 ± 3.38; p = 0.940) or homocysteine (7.90 ± 1.79 vs. 8.15 ± 2.70 µmol/L; p = 0.290). Conclusion: Vitamin D supplementation (2,000 IU/day) effectively restores 25(OH)D levels and improves adiponectin and hs-CRP in epilepsy patients on enzymatic ASMs, suggesting a potential benefit for cardiovascular risk reduction. However, vitamin D alone did not prevent the rise in homocysteine, likely due to the concurrent cessation of B-vitamin supplementation.
Keywords: anticonvulsants; cholecalciferol; C-reactive protein; insulin resistance